Pengaruh Keamanan dan Kenyamanan terhadap Niat Masyarakat untuk Beralih dari Penggunaan Bank Konvensional ke Bank Digital - Aulia, Shandina; Arlina Hakim, Siska; Sophia Marsiska (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to find out the security and convenience that influences people to switch from the use of conventional banking to digital banking and to know the people’s intention to switch to using digital banks. This type of research is primary data research, data that is processed as number obtained from the scale of questionnaires that the researcher spread to respondents, and porsessed using SPSS 26 Software. The sample in this study amounted to 109 respondents. Research result show that security (X1) and convenience (X2) affect the (Y) intention of people to switch to digital banking